Binding characterization of anthraquinone derivatives by stabilizing G-quadruplex DNA leads to an anticancerous activity - Arpita Dey; Kumud Pandav; Mala Nath; Ritu Barthwal; Ramasare Prasad (Molecular Therapy: Nucleic Acids, 2022)
G-quadruplex is a non-canonical secondary structure identified in the telomeric region and the promoter of many oncogenes. Anthraquinone derivatives, a well-known inducer of telomere disruption in malignant cells and activate the apoptotic pathway. We used biophysical and biochemical studies to confirm the interaction of synthesized anthraquinone derivatives with the human telomeric G-quadruplex sequence. The binding affinity of N-2DEA and N-1DEA are Kb = 4.8 × 106 M−1 and Kb = 7.6 × 105 M−1, respectively, leading to hypochroism, fluorescence quenching with minor redshift and ellipticity variations indicating ligand binding in the external groove. We found that sodium ions induced stabilization more rather than potassium ions. Molecular docking of complex demonstrates a molecule’s exterior binding to a quadruplex. The investigation of ROS activity indicated that the cell initiates mortality in response to the IC50 concentration. Cellular morphology, nuclear condensation, and fragmentation were altered in the treated cell, impairing cellular function. Finally, the transcriptional regulatory study paves the way for drug design as an anti-cancer agent because of the tremendous possibilities of changing substituent groups on anthraquinones to improve efficacy and selectivity for G-quartet DNA. Our research focused on how ligand binding to telomere sequences induces oxidative stress and inhibits the growth of malignant cells.